New university processes: challenges for the improvement of teaching and reflective teaching practices - Muñoz, Francisco Imbernón; Valenzuela, Carolina Guzmán (Revista Hipótese, 2015)
Through this research, qualitative, we conducted a monitoring of teaching practices performed by two junior professors at the University of Barcelona belonging to two different disciplinary fields (area of health sciences and the humanities) and , from here, one of the objectives was to identify whether the teachers, despite their short experience in the field of education, were able to launch reflexive processes that enable them to make decisions and / or change its course while they are teaching action or after it and opens possibilities for change and professional development. The results of this research serve, in our view, to focus our attention on teaching at the University and its improvement through thoughtful analysis that processes early, accompanied by the knowledge that starts faculty when she teaches college.
Keywords: Novel university professors; teaching practices; epistemology of practice; reflexive processes; training the inexperienced teacher